Segregation of Re at the γ/γ′ boundary of Ni-based single crystal superalloys revealed by first-principles calculations based Monte-Carlo simulations. (20th April 2023) - Zhu, Heyu; Wang, Jiantao; Wang, Lei; Shi, Yongpeng; Liu, Mingfeng; Li, Jiangxu; Chen, Yun; Ma, Yingche; Liu, Peitao; Chen, Xing-Qiu
Highlights: An accurate cluster expansion derived Monte-Carlo interatomic potential for the Ni–Al–Re system has been developed to clarify the Re distributions and its influence on the disorder-order transition temperatures of superalloys. Monte-Carlo simulated annealings of Ni–Al–Re alloys show that most of Re atoms stay in the γ phase, while a few of Re atoms stay in the γ ′ phase. Addition of Re increases the disorder-order transition temperature of the Ni–Al–Re alloys. Localized supersaturation of Re at the γ / γ ′ boundary is observed. Abstract: Nickel-based single crystal superalloys have been widely used in aero-engines and gas turbine engines. To improve the creep resistance, rhenium is often added to the alloys. However, it is not yet fully understood how the added Re elements distribute in the alloys and how the microstructure evolves with the addition of Re. Here, we performed extensive first-principles calculations based Monte-Carlo simulated annealing of Ni–Al–Re ternary alloys with different Re concentrations ranging from 0.5 at.% to 6.0 at.%. The results demonstrate that with the decreasing temperature, most of Re atoms stay in the γ phase, while a few of Re atoms stay in the γ′ phase and tend to occupy the Al positions. At low temperatures, the Re atoms segregate at the γ/γ′ boundary, in good agreement with experiment. We find that the disorder-order transition temperature of the Ni–Al–Re ternary alloys increases with the Re concentration due to the Re-enhanced Al–Al ordering tendency. In addition, we observe that at low temperatures the Re segregation at the γ/γ′ boundary promotes the formation of Ni4 Re- or Ni8 Re-like local structures as the Re concentration is over 2 at.%. The formation of a large amount of these local structures consumes the Re atoms in solid solutions, and thus from the solid-solution strengthening point of view, this would have a negative influence on the creep resistance of the superalloys. This work provides important atomistic insights on the Re distribution and its effects on the stability of superalloys. Graphical Abstract: Image, graphical abstract